Effects of Vitamin D and Body Mass Index on Disease Risk and Relapse Hazard in Multiple Sclerosis: A Mendelian Randomization Study. Issue 3 (7th May 2022) - Vandebergh, Marijne; Dubois, Bénédicte; Goris, An
Abstract : Background and Objectives: Decreased vitamin D levels and obesity are associated with an increased risk for multiple sclerosis (MS). However, whether they also affect the disease course after onset remains unclear. With larger data sets now available, we used Mendelian randomization (MR) to determine whether serum 25-hydroxyvitamin D (25OHD) and body mass index (BMI) are causally associated with MS risk and, moving beyond susceptibility toward heterogeneity, with relapse hazard. Methods: We used genetic variants from 4 distinct genome-wide association studies (GWASs) for serum 25OHD in up to 416, 247 individuals and for BMI from a GWAS in 681, 275 individuals. Applying 2-sample MR, we examined associations of 25OHD and BMI with the risk of MS, with summary statistics from the International Multiple Sclerosis Genetics Consortium GWAS in 14, 802 MS cases and 26, 703 controls. In addition, we examined associations with relapse hazard, with data from our GWAS in 506 MS cases. Results: A 1-SD increase in genetically predicted natural-log transformed 25OHD levels decreased odds of MS up to 28% (95% CI: 12%–40%, p = 0.001) and decreased hazard for a relapse occurring up to 43% (95% CI: 15%–61%, p = 0.006). A 1-SD increase in genetically predicted BMI, corresponding to roughly 5 kg/m 2, increased risk for MS with 30% (95% CI: 15%–47%, p = 3.76 × 10 −5 ). On the contrary, we did not find evidence for a causal role of higher BMI with an increased hazard for occurrence of a relapse. Discussion: This study supports causal effects of genetically predicted serum 25OHD concentrations and BMI on risk of MS. In contrast, serum 25OHD but not BMI is significantly associated with relapse hazard after onset. These findings might offer clinical implications for both prevention and treatment.